Can gait kinetic data predict femoral bone mineral density in elderly men and women aged 50 years and older?. (23rd June 2021) - Choi, Wooyoung; Choi, Ji Hye; Chung, Chin Youb; Sung, Ki Hyuk; Lee, Kyoung Min
Abstract: This retrospective study was conducted to investigate the correlation between kinetic gait parameters and femoral bone mineral density (BMD) in elderly subjects aged 50 years and older that could walk independently. Four hundred and twenty-six subjects (158 men and 258 women; mean age 68.7 years, standard deviation (SD) 7.9 years) were included in the study. BMDs (g/cm 2 ) of the femoral neck, trochanter, shaft, and total proximal femur were collected. Kinetic data including maximum hip power and hip power-time integral was obtained from a three-dimensional gait analysis with self-selected walking speed. Correlation between BMDs of proximal femur and gait kinetic data was analyzed. Multiple regression analysis was also performed to identify factors significantly associated with BMD. Correlation between BMD and hip kinetic data was not prominent in elderly men. In women, BMD was significantly correlated with hip kinetic data. Hip power-time integral showed greater correlation with BMD than maximum hip power during gait in elderly women. Age (p < 0.001), weight (p = 0.007) and hip power-time integral (p = 0.008) were significant factors associated with femoral neck BMD, and these factors explained 25.4% of femoral neck BMD. In conclusion, the association between the mechanical load and BMD in the different sexes provokes future research into these issues. The effects of various types of exercises on BMD should be investigated more precisely using a gait analysis tool.